2022
DOI: 10.3389/fcell.2021.787278
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Alleviates Intervertebral Disc Degeneration via Restoring Autophagy Flux in Nucleus Pulposus Cells

Abstract: Oxidative stress–induced apoptosis and senescence of nucleus pulposus (NP) cells play a crucial role in the progression of intervertebral disc degeneration (IVDD). Accumulation of studies has shown that activated autophagy and enhanced autophagic flux can alleviate IVDD. In this study, we explored the effects of apigenin on IVDD in vitro and in vivo. Apigenin was found to inhibit tert-butyl hydroperoxide (TBHP)–induced apoptosis, senescence, and ECM degradation in NP cells. In addition, apigenin treatment can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…Following transfection with siRNA-TFEB, apigenin failed to inhibit the senescence of NP cells induced by THBP. 96 What's more, Wang et al 97 reported that parathyroid hormone 1-34 (PTH) could inhibit the mTOR signalling pathway, promote autophagy in rat NP cells, and suppress NP cell senescence; transfection of siRNA-ATG5 inhibited autophagy, and the protective effect of PTH was abolished. These studies suggest that inhibition of the mTOR pathway might suppress NP cell senescence.…”
Section: Mtor Signalling and Ecm Degradation In Npmentioning
confidence: 99%
“…Following transfection with siRNA-TFEB, apigenin failed to inhibit the senescence of NP cells induced by THBP. 96 What's more, Wang et al 97 reported that parathyroid hormone 1-34 (PTH) could inhibit the mTOR signalling pathway, promote autophagy in rat NP cells, and suppress NP cell senescence; transfection of siRNA-ATG5 inhibited autophagy, and the protective effect of PTH was abolished. These studies suggest that inhibition of the mTOR pathway might suppress NP cell senescence.…”
Section: Mtor Signalling and Ecm Degradation In Npmentioning
confidence: 99%
“…The autophagy level was higher in degenerative NPCs compared with normal NPCs, which indicated that autophagy might be involved in the deterioration of IDD [55]. Many investigations have indicated that autophagy was an important protective factor for IVD, and the restoration of autophagy was a promising research direction in IDD [13,[56][57][58]. Some studies have indicated that MSCs could significantly increase the autophagy level, and reduce the apoptosis of NPCs [25,59].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, circKIF18A suppressed the proteasomal degradation of mini-chromosome maintenance complex component 7 (MCM7) [ 39 ]. In addition, other exogenous oxidative stressors such as tert-butyl hydroperoxide (TBHP) are widely used in NP cells to induce premature CS signaling in cultured cells [ 43 , 44 , 45 ]. The DNA damage caused by oxidative stress is sensed by the stimulator of interferon genes (STING) pathway to regulate senescence in NP cells [ 46 ].…”
Section: Disc Cell Senescence Under Various Stressorsmentioning
confidence: 99%